Worldwide Scientific Production Indexed by Scopus on Labour Relations - Salmerón-Manzano, Esther; Manzano-Agugliaro, Francisco (Publications, 2017)
This article examines the features of the worldwide contributions to the specialized literature in labour relations in the period 1970–2016. The source considered has been the Scopus Elsevier database, together with bibliometric analysis techniques. Different aspects of the publications are analysed, such as publication type, field, language, subcategory and journal type, as well as the keyword occurrence frequency. The results of this work show that the most popular keywords were Trade Union, Employment, Labour Market and Industrial Relations. It is observed how the United States, being the most productive country, leads in almost all the keywords except in two, “Labour market” and “Working Conditions”, which are led by UK. If the keywords are studied only as geographical terms we can find the United States, Eurasia and India. The contributions are geographically and institutionally broken down. The most active categories are Social Sciences, Business, and Management and Accounting. The evolution of the most popular keywords indicates how in the last years “Trade Unions” “Industrial Relations” and “Personnel” have lost importance against “Labor Market” and “Employment”, showing new concerns in the labour relations field.
Keywords: labour relations; scientometric; worldwide; Scopus; Emerging